Study of the structure and properties of the lanthanides tetrakis-compounds with N-(bis-(benzylamino)phosphoryl)-tosylamide - Prytula, А.Yu.; Trush, V.A.; Sliva, T.Yu.; Litsis, О. О.; Nedilko, S.G.; Amirkhanov, V.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The new ligand N-(bis(benzylamino)phosphoryl)-tosylamide (HL) and the neutral salt NaL on its base have been synthesized. Coordination compounds of lanthanides are separated in the individual state by the general formula Na[LnL4]. They have been studied by the methods of IR, NMR, and electronic spectroscopy. Based on these data, the coordination mode of ligands and the composition of coordination compounds have been suggested. The efficient europium photoluminescence has been confirmed in the Na[EuL4] solid state complex.